Initial experience of magnetic seed localization for impalpable breast lesion excision: First 100 cases performed in a single Irish tertiary referral centre. Issue 3 (June 2022) - Murphy, Edward; Quinn, Edel; Stokes, Maurice; Kell, Malcom; Barry, Mitchel; Flanagan, Fidelma; Walsh, Siun M.
Abstract: Introduction: Wire guided localization has been widely utilized as the standard method of pre-operative localization of breast lesions. Magnetic seeds were developed to counter some of the disadvantages associated with wires. This aim of this study was to assess outcomes following the introduction of magnetic seeds at a tertiary specialist breast centre. Methods: A retrospective review of a prospective database of the first 100 patients who underwent magnetic seed (Magseed) guided breast surgery between November 2018 and November 2019. Data was collected from 17 wire guided cases completed during the trial phase for comparison. The primary outcome measures were successful excision of index lesion and retrieval of the magnetic seed. Secondary outcomes analyzed included time ready for theatre, post-operative complications and breast margin re-excision rate. Results: Of these 100 cases, 85 patients underwent Magseed guided wide local excision for invasive or in-situ carcinoma and 15 underwent Magseed guided diagnostic excision. The primary lesion was excised, and Magseed was retrieved in all 100 cases. 54% of patients were ready to proceed as the first scheduled theatre case of the day, compared to 0% of wire-guided cases. Amongst therapeutic Magseed guided cases, the re-excision rate for margin clearance was 9.4%. Conclusion: Magseed guided breast excision is a new technology that has been implemented with relative ease in our unit. We have shown that magnetic seed guided surgery reliably localizes lesions, is associated with low re-excision rates without an increase in patient morbidity or mortality and results in improvements in theatre planning and efficiency. Highlights: Magnetic seed localisation. Introduction of new surgical technology. No increase in post-operative complications or re-excision rates. Improved theatre efficiency and timing.